Principal Leadership in Growing a Culture of Discipline - Nurhemah, Neng; Putri, Mas Fierna Janvierna Lusie (CV. Rayyan Dwi Bharata, 2025)
This study aims to examine the leadership role of school principals in fostering a culture of discipline in the school environment. Using a qualitative approach and literature study method, this research examines various relevant literature, journals, and regulations to illustrate effective leadership strategies. The results indicate that principals have a central role in shaping a culture of discipline through exemplary leadership, clear policy planning, involvement of all school members, and continuous evaluation. Transformational and democratic leadership styles are considered the most effective in building discipline awareness that grows from within the school community. Strategies such as teacher empowerment, student involvement, and cooperation with parents also strengthen the implementation of disciplinary values. And the study results describe the planning, implementation, and evaluation strategies of school principals in fostering a culture of discipline. The findings confirm that strong and consistent principal leadership is key in creating an orderly, positive, and characterful educational environment.